Spatiotemporal and Functional Heterogeneity of Hematopoietic Stem Cell-Competent Hemogenic Endothelial Cells in Mouse Embryos - Li, Yun-Qiao; Gong, Yandong; Hou, Siyuan; Huang, Tao; Wang, Haizhen; Liu, Di; Ni, Yanli; Wang, Chaojie; Wang, Junliang; Hou, Jun; Yang, Ruichuang; Yan, Jing; et al. (Frontiers in Cell and Developmental Biology, 2021)
Hematopoietic stem cells (HSCs) are derived from hemogenic endothelial cells (HECs) during embryogenesis. The HSC-primed HECs increased to the peak at embryonic day (E) 10 and have been efficiently captured by the marker combination CD41-CD43-CD45-CD31+CD201+Kit+CD44+ (PK44) in the aorta-gonad-mesonephros (AGM) region of mouse embryos most recently. In the present study, we investigated the spatiotemporal and functional heterogeneity of PK44 cells around the time of emergence of HSCs. First, PK44 cells in E10.0 AGM region could be further divided into three molecularly different populations showing endothelial- or hematopoietic-biased characteristics. Specifically, with the combination of Kit, the expression of CD93 or CD146 could divide PK44 cells into endothelial- and hematopoietic-feature biased populations, which was further functionally validated at single cell level. Next, PK44 population could also be detected in the yolk sac, showing similar developmental dynamics and functional diversification with those in the AGM region. Importantly, PK44 cells in the yolk sac demonstrated an unambiguous multi-lineage reconstitution capacity after in vitro incubation. Regardless of the functional similarity, PK44 cells in the yolk sac displayed transcriptional features different to those in the AGM region. Taken together, our work delineated the spatiotemporal characteristics of HECs represented by PK44, and revealed a previously unknown HSC competence of HECs in the yolk sac. These findings provided a fundamental basis for in-depth studying the different origins and molecular programs of HSC generation in the future.